Design of a single-carrier pulse width modulation with submodule fault-tolerant capability for modular multilevel converter / Tuanku Badzlin Hashfi - Tuanku Badzlin, Hashfi (2020)
Multilevel converters are attracting a lot of attention and becoming one of the energy conversion choices for new topologies and control in industry applications and research fields. Modular multilevel converters (MMCs) are considered very promising among converter topologies for future medium-voltage and high-power applications compared to NPC, FC and CHB topologies. The improved phase disposition pulse width modulation (PDPWM) technique control for MMCs, which has a fault-tolerant capability, is presented. This study presents two methods to distribute pulses into submodules (SMs) by using PDPWM which has drawback to distribute the power equally among the submodules (SMs). First method, this study used conventional PDPWM to distribute the power equally among the SMs. Second, this study utilized one single carrier that can improve modulation strategy that has flexibility for fault-tolerant capability. Fault tolerance can enhance converter reliability, which is one of the essential issues of half-bridge MMCs with substantial switching devices. An excellent overall control system is also required for MMCs to rebalance the capacitor after a fault. An understanding of the basic operating principle is essential in order to find the dimensioning factors of modular multilevel converter (MMC). The dimension of MMC was designed in MATLAB/Simulink by ensuring the performance is well governed in circulating current and energy balance for closed-loop control. The improvement of modulation technique was tested in a simulation platform and hardware implementation. In this study, an MMC with a fault condition was analyzed. Afterward, a modulation control for the fault-tolerant method was proposed and described in detail. The proposed method bypassed the faulty SM when a faulty switching device occurs in an SM. The proposed method was tested in MATLAB/Simulink platform to verify the proposed method in the simulation platform. Experimental results were included to verify the fault-tolerant capability of the proposed modulation strategy for MMCs.